Zastosowanie algorytmu poprawki (Adjustment Algorithm) do konstrukcji planów D-optymalnych przy ograniczeniach kosztowych - Kuźmiński, Łukasz (The implementation of adjustment algorithm to create the D-cost-optimal. Real design at limited cost, 2008)
The paper describes the modified adjustment algorithm for seeking the real designs according to the definite criterion (/-optimality at limited costs intended for realization of the experiment. An example of running the described algorithm is shown in the paper. In presented example, the exercise consists in assigning the ￡>-cost-optimal, real design of experiment for estimating parameters of the regression function equation with one explanatory variable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 162-174